Kontribusi Ulama Andalusia Dalam Pembentukan Mazhab Nahwu - Zufar Yoy Fakhri; Nazla Ramadhani Gunawan; Ihwanul Khoiron; Muhammad Sulthon Aulia (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to uncover the history of the development of nahwu science in Andalusia, as well as the contributions of Andalusian figures in enriching Arabic language studies. The main focus lies on the process of the entry of nahwu science into the Andalusia region, the nahwu schools that developed there such as Basrah, Kufa, and Baghdad, and the role of local scholars in developing and criticizing classical nahwu theories. Andalusia as the center of Islamic civilization in the West played an important role in the spread of knowledge, including in the field of Arabic grammar. Figures such as Yahya bin Yahya, Ibn Quthayyah, Ibn Hazm, and Ibn Maḍāʾ al-Qurṭubī made great contributions to the dynamics and simplification of nahwu science. Through a historical and qualitative descriptive approach, this study attempts to trace these developments based on primary and secondary sources from classical Islamic literature. The results of the study show that the characteristics of the science of nahwu in Andalusia tend to be more practical, contextual, and critical compared to schools of thought in the East. This finding shows that the dynamics of science in Andalusia are progressive and adaptive to the needs of its society.